Genetic analysis of F2 population of tomato for studying quantitative traits in the cross between Bushbeef x Nagina - Mehboob Ahmad; Mazhar Iqbal; Zishan Gul; Bilal Ahmed Khan; Muhammad Shahid; Maria saleem; Nayyer Iqbal Khan (Journal of Research in Biology, 2016)
This study aims to determine the genetic components like Vg(Variance of genotype), Vp ( Variance of phenotype), GCV (Genotypic co-efficient of variation), PCV (Phenotypic coefficient of variation), Hb (Heritability) and GA% (Genetic advance in percentage of means) in F2 generation of the cross Nagina x Bushbeef-steak for predicting quantitative traits. Data was collected on P1, P2 F1 and F2 generation for various yield components and were analyzed. Analyzed data showed relatively high difference between, GCV, Vp and PCV for the traits: Flowers/cluster, Fruits/cluster and Fruit weight and relatively low difference was noted for Vg, GCV and Vp, PCV values in the traits: Fruit diameter, Fruit length and fruits/plant. Highest value of GCV (79.90%) and PCV (92.79%) were noted in the trait: yield/plant and the lowest values of GCV (14.68%) and PCV (16.78%) were noted for fruit-length. Highest value (84.08%) of broad sense heritability %(Hb%) was noted in fruit diameter and the lowest value of heritability(27.58) was noted for the trait fruits/cluster. Moderate value of heritability (74.13%) along with low value (15.22) of GA% was noted for yield/plant.